qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = x - 3$
$y = 2 x - x + 3$
$x$Intercept
$\left ( 3 , 0 \right )$
$y$Intercept
$\left ( 0 , - 3 \right )$
$x$Intercept
$\left ( - 3 , 0 \right )$
$y$Intercept
$\left ( 0 , 3 \right )$
$x-3 = 2x-x+3$
$ $ Do not have the solution $ $
Solve the equation
$x - 3 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ x } + 3$
$ $ Calculate between similar terms $ $
$x - 3 = \color{#FF6800}{ x } + 3$
$x - 3 = \color{#FF6800}{ x } + 3$
$ $ Move the variable to the left-hand side and change the symbol $ $
$- 3 = 3$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } = \color{#FF6800}{ 3 }$
$ $ This equation is false because all of the values calculated by all terms are different $ $
$ $ Do not have the solution $ $
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo